2016
DOI: 10.1007/s10353-016-0457-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and angiogenesis in primary hyperparathyroidism

Abstract: SummaryBackgroundThe inappropriate elevation of parathormone (PTH), which regulates the process of angiogenesis in parathyroid tissue, causes the changes of activity of enzymes responsible for the removal of free radicals. Parathyroidectomy (PTX) in patients with primary hyperparathyroidism (PHPT) lowers the level of PTH and leads to the reduction of risk of cardiovascular and all-cause mortality by normalization of the antioxidant status. Therefore, the aims of the study were to assess the activity of antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 70 publications
0
6
0
2
Order By: Relevance
“…Among the candidate mechanisms able to induce endothelial dysfunction, we chose to investigate the role of ROS since the presence in literature of indirect evidence about the relation between PTH levels and markers of oxidative stress [22, 23]. We found that PTH induces mitochondrial ROS production in a calcium-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the candidate mechanisms able to induce endothelial dysfunction, we chose to investigate the role of ROS since the presence in literature of indirect evidence about the relation between PTH levels and markers of oxidative stress [22, 23]. We found that PTH induces mitochondrial ROS production in a calcium-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms contribute to endothelial dysfunction, and among these, the oxidative stress seems to have a determinant role; indeed, sustained ROS production can inactivate nitric oxide (NO), thus contributing to impaired endothelial-dependent vasodilatation [20]. The potential regulation of ROS production by PTH has been hypothesized [21], since after parathyroidectomy in patients, the decrease of oxidative stress markers occurs [22, 23]. However, a mechanistic link between PTH and altered redox balance is still to be verified.…”
Section: Introductionmentioning
confidence: 99%
“…Malondialdehyde (MDA) is a common lipid peroxidation product and reflects the level of ROS produced by lipid oxidation, which, in turn, indirectly reflects the degree of oxidative damage in tissues and cells. Therefore, SOD and MDA are commonly used to evaluate the level of oxidative stress in cells [ 27 ]. It could be shown that the internal oxidation became unbalanced as the level of blood Scr rose.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress-induced angiogenesis has been well established and its intermediate regulatory medium is VEGF. 50,51 Combet et al confirm an independent contribution of uremia in the peritoneal changes during PD, especially for peritoneal neoangiogenesis, with increased levels of peritoneal nitric oxide synthase (NOS) isoform, AGEs and VEGF from a rat model of subtotal nephrectomy. 52 Enhanced NOS activity and endothelial NOS up-regulation are considered as a reasonable explanation for peritoneal morphologic changes (angiogenesis and increased endothelial area), which are based on the biologic relevance between NOS and vascular density.…”
Section: Uremiamentioning
confidence: 99%